The Role of Information and Communication Technology (ICT) in Enhancing Educational Accessibility and Quality in Indonesia’s 3T Regions - Eka Sriwahyuni; Sherly Desliyanah; Mawarda Nurodanika (Gateway for Understanding Research in Education, 2025)
This study investigates The Role of Information and Communication Technology (ICT) in Enhancing Educational Accessibility and Quality in Indonesia's 3T Regions. Employing a descriptive qualitative methodology, data were collected through triangulation participant observation, semi-structured interviews, and documentation involving key stakeholders (teachers, students, and officials) in Eastern Indonesia. Findings confirm that ICT significantly overcomes geographical constraints by facilitating access to diverse learning resources and enabling effective distance learning, subsequently boosting digital literacy and student engagement. However, the study identifies persistent barriers in infrastructure gaps (connectivity, device scarcity) and human resource capacity (techno-pedagogical competence) that hinder optimal integration. This research underscores the necessity of a systemic strategy combining resilient infrastructure development, continuous teacher training, and localized policy to achieve sustainable educational equity.